Successful Outcome of Patellectomy Plus Chemotherapy for Primary Bone Lymphoma of the Patella: A Case Report and Literature Review - Cao, Xin; Chen, Hui-Jin (Frontiers in Oncology, 2021)
Primary bone lymphoma (PBL) is a rare but distinct clinicopathological disease, usually occurring in the pelvis, spine, and ribs. To date, only a few cases have been reported as beginning in the patella. Due to the lack of clinical evidence, the optimal treatment strategy has not been established. Here, we report a case that presented unexplained right knee pain. The case was diagnosed with the non-germinal center, diffuse large B cell lymphoma in the patella by imaging examinations and bone biopsy. Then, the patient received a patellectomy and eight cycles of R-CHOP chemotherapy. After treatment, the patient achieved a favorable prognosis and satisfactory functional recovery.